2013
DOI: 10.1002/ldr.2248
|View full text |Cite
|
Sign up to set email alerts
|

Revegetation of Decomposed Granite Roadcuts in Korea: Developing Digger, Evaluating Cost Effectiveness, and Determining Dimensions of Drilling Holes, Revegetation Species, and Mulching Treatment

Abstract: Decomposed granite roadcuts are difficult to revegetate after losing the topsoil and vegetation cover. We developed a new drilling machine, Digger, to efficiently drill six holes simultaneously on decomposed granite roadcuts to facilitate revegetation. The Digger consists of a base machine (0.7 m3‐level excavator) and a mounting body with six hydraulic motors instead of a bucket. We tested its performance on two roadcuts in southwest Korea using time‐motion studies, which showed that the Digger can drill 240 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 74 publications
0
46
0
Order By: Relevance
“…Most plant mortalities occurred during the first summer, which was the driest of the 3 years, and occurred very little during the following summer droughts. Another approach could be to associate seeding with drilling holes, as was experimented by Lee et al (2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most plant mortalities occurred during the first summer, which was the driest of the 3 years, and occurred very little during the following summer droughts. Another approach could be to associate seeding with drilling holes, as was experimented by Lee et al (2013).…”
Section: Discussionmentioning
confidence: 99%
“…Planting and seedling methods for installing vegetation on slopes are therefore required. Such methods have already been tested on several other eroded lands (Reubens et al, 2009;Bochet et al, 2010;Fernández et al, 2012;Commander et al, 2013;Lee et al, 2013), but these studies did not apply to our climatic, topographic and pedological conditions, and the studied plant species are not appropriate or currently available. Therefore, the main issue for practitioners is to find the adequate solution to develop vegetation cover on gully slopes.…”
Section: Breton Et Al: Effects Of Wood Chip Amendments On the Revmentioning
confidence: 99%
“…On the other hand, however, when roads penetrate into (or are improved in) areas, they may intensify efforts to exploit resources (Deng et al, 2011) and therefore cause KRD deterioration (Mick, 2010;Yang et al, 2013). Road construction can create numerous roadcuts and embankments that can contribute to increased sediment production and further cause land degradation (Lee et al, 2013). Serious soil erosion can occur on bare road embankments (especially those under construction) (Cerdà, 2007) and on unpaved roads (Cao et al, 2013b).…”
Section: Discussionmentioning
confidence: 99%
“…Serious soil erosion can occur on bare road embankments (especially those under construction) (Cerdà, 2007) and on unpaved roads (Cao et al, 2013b). Restoration efforts should be directed to guarantee key ecological processes and support soil formation for roadcuts and embankments (Jimenez et al, 2013;Lee et al, 2013). New strategies should emphasize the need to decrease the impact of road construction on plant and animal habitats and the benefits of using local species for the re-vegetation of land surrounding the roads (Cheng et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, straw mulch was confirmed to have a positive effect on water quality (Faucette et al, 2007) and the mitigation of wind-induced soil erosion (Nelson, 2002). Low mulch cover was also found to be efficient by researchers who dealt with road embankments protection (Lee et al, 2013), afforested land (Jiménez et al, 2013) and agricultural soils (Jordán et al, 2010). In addition, García-Moreno et al (2013) reported that excessive mulch rates (9-12 Mg ha −1 yr.…”
Section: Tablementioning
confidence: 99%